Rancang Bangun Sistem Keamanan Helm dan Berkendara Berbasis Mikrokontroler - Demita, Syukurillah Paradiqma; Yendri, Dodon; Suwandi, Rifki (CHIPSET, 2024)
As a two-wheeled vehicle user, a problem that often occurs in the community is the loss of helmets when placed in the parking lot. This can happen due to lack of attention from security personnel at the parking location. Riders who do not use helmets can endanger themselves in the event of an accident. In addition to the use of helmets, speed in driving is one factor that needs to be considered because it has the potential to endanger yourself or others. This study aims to anticipate the occurrence of helmet theft and also provide safety in driving using survey research methods to determine the percentage of ease of use by users. Where the system designed consists of 4 functions, namely, detection of helmet location using the MQTT protocol where if the helmet position with the vehicle has a large distance of 40m then the helmet is detected to have been stolen so that it will issue a warning in the form of sound. The second system is vehicle speed detection using anemometer sensors, if the vehicle is detected to have a large speed of 50km / h then the helmet will issue a sound warning so that the driver can reduce driving speed. The third system is face detection around the helmet using ESP32-Cam, where if the helmet detects an unknown face through the face recognition feature with a distance of 15cm to 60cm from the helmet, the ESP32-Cam will take pictures. The last system is taking pictures periodically to find out the situation around the helmet. Based on research using a questionnaire with 30 samplers, a percentage of 74.95% was obtained, which means that the helmet is easy to use.